(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the theoretical foundations and methodological approaches to developing students’ reading activity in primary school mother tongue lessons. The structure of reading activity and the ways of forming conscious, expressive, and fluent reading skills are discussed. The effectiveness of interactive methods and modern pedagogical technologies in improving reading competence is also substantiated.